Nematic topological superconducting phase in Nb-doped Bi2Se3. Issue 1 (December 2017) - Shen, Junying; He, Wen-Yu; Yuan, Noah; Huang, Zengle; Cho, Chang-woo; Lee, Seng Huat; Hor, Yew San; Law, Kam Tuen; Lortz, Rolf
Abstract A nematic topological superconductor has an order parameter symmetry, which spontaneously breaks the crystalline symmetry in its superconducting state. This state can be observed, for example, by thermodynamic or upper critical field experiments in which a magnetic field is rotated with respect to the crystalline axes. The corresponding physical quantity then directly reflects the symmetry of the order parameter. We present a study on the superconducting upper critical field of the Nb-doped topological insulator Nbx Bi2 Se3 for various magnetic field orientations parallel and perpendicular to the basal plane of the Bi2 Se3 layers. The data were obtained by two complementary experimental techniques, magnetoresistance and DC magnetization, on three different single crystalline samples of the same batch. Both methods and all samples show with perfect agreement that the in-plane upper critical fields clearly demonstrate a two-fold symmetry that breaks the three-fold crystal symmetry. The two-fold symmetry is also found in the absolute value of the magnetization of the initial zero-field-cooled branch of the hysteresis loop and in the value of the thermodynamic contribution above the irreversibility field, but also in the irreversible properties such as the value of the characteristic irreversibility field and in the width of the hysteresis loop. This provides strong experimental evidence that Nb-doped Bi2 Se3 is a nematic topological superconductor similar to the Cu- and Sr-doped Bi2 Se3 . Topological superconductors: unveiling the nature of the superconductive pairing The superconducting phase of Nb-doped Bi2 Se3 is nematic, that is, it has a 2-fold symmetry that breaks the 3-fold symmetry of the crystal. Topological insulators, such as Bi2 Se3, can become superconductive when doped, which is interesting because topological superconductors host Majorana fermions, which hold potential for quantum computation. However, the nature of the superconductive pairing in these materials is debated. To settle the question for Nb-doped Bi2 Se3, a team led by Rolf Lortz at the Hong Kong University of Science and Technology measured the dependence of the superconducting upper critical field on the orientation of an applied magnetic field. These measurements demonstrate that Nb-doped Bi2 Se3 has an odd-parity nematic superconducting phase, as further supported by the fact that the data can be fitted with a model for nematic superconductivity.